Consumer Perception of Barista Services in Pare-Pare City - Wim J Winowatan; I Putu Suarta; Murdiani Sukarana (Publik : (Jurnal Ilmu Administrasi), 2021)
The purpose of this study is to determine consumer perceptions of barista services in Parepare City, South Sulawesi Province. The method in this study is qualitative using a descriptive approach. The method of data collection in this study was done through observation, interviews with a list of questions, and documentation. The results of the study indicate that consumer perceptions of Barista services have not been maximally reached in general, including the aims and objectives. Baristas do not understand the importance of consumer perceptions of service, especially services in blending coffee drinks. This needs to be followed up so that consumers or guests can better understand the existence and services of Baristas, this is because consumers or guests as coffee drinkers are not coffee connoisseurs and only choose the type of coffee provided. and still lack the availability of very limited and expensive equipment that is spent on each equipment needed.